Does â€œExperienceâ€ Bring about Any Significant Difference in EFL Teacher Talk? - Doqarun, Vahid Rahmani; Khodadady, Ebrahim (Beyond Words, 2016)
The rationale for the present study is based on the fact that understanding the teaching pro-cess and the development of teachers is incomplete unless the teachers' classroom behavior, especially their talk, is objectively explored. To this end, four male teachers offering Eng-lish as a foreign language (EFL) were recruited and divided into two groups, namely inex-perienced and experienced. To secure the objectivity in data collection they were observed in their classes and one lesson of each teacher was audio-recorded. The audio-recordings were then fully transcribed and analyzed through micro structural approach of schema theo-ry. The approach is based on the assumption that any word uttered by the teacher represents a specific concept commonly known as a schema. The schema enters into a hierarchical re-lationship with other schemata to constitute species, genera and semantic, syntactic and parasyntactic domains of language. The teachersâ€™ talks were thus parsed into their constitut-ing schema types, species, genera and domains and certain codes were assigned to them to run statistical analyses. The findings showed that the inexperienced teachers significantly outnumbered their experienced counterparts in all schema categories and thus challenged â€œexperienceâ€ as an effective variable in EFL teaching